Gender pay gaps in Morocco: urban-rural disparities across the wage distribution - Fatima Mounir; Said Hanchane; Khalid Soudi (Development Studies Research, 2025)
Gender pay gaps persist as a significant feature of labor markets in developing countries, with disparities varying across the wage distribution and between urban and rural areas. Using data from the 2012, 2015, and 2017 Labor Force Surveys, we investigate wage discrimination and its implications for women's labor force participation, incorporating corrections for potential selection bias. Beyond the traditional Oaxaca–Blinder decomposition, we employ the Recentered Influence Function decomposition to analyze gaps across the distribution. Our results show that wage gaps are more pronounced at the lower end of the distribution, suggesting that women face significant challenges in securing equal compensation and advancing in their careers. However, once they reach leadership positions, they tend to earn comparable wages. Complementary Oaxaca–Blinder decompositions reveal a significant gender wage gap in urban areas, with women earning 8.3% and 3.4% less than men in 2012 and 2017, respectively. The unexplained gap, often associated with potential discrimination, decreased from 25% to 11% over the period. In rural areas, the gap reached 41.8% in 2012 and 25.4% in 2017, indicating a narrowing trend. Our results highlight the need for targeted public policies to address the structural barriers women face, particularly in low-paid jobs and rural labor markets.